The Influence of Celebrity Endorsement and Testimonials on Buying Interest in The Originote Skincare Product for Students in Ngawi District - Kusumaningtyas, Arnida; Suranto, S; Ulfatun, Titik (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the influence of celebrity endorsement and consumer testimonials on the purchasing intention of The Originote skincare products among university students in Ngawi Regency. The research employs a quantitative approach using a survey method. The population consists of students in Ngawi Regency, with a sample of 100 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression to assess the relationship between celebrity endorsement and testimonials on purchase intention. The results indicate that both variables have a positive and significant effect on consumers' purchasing intention. Celebrity endorsement exerts a stronger influence, particularly when the chosen celebrity holds a strong and favorable image among consumers. Additionally, credible consumer testimonials also contribute positively by enhancing trust and purchase interest. The findings suggest that celebrity endorsement and testimonials are effective strategies to boost purchasing intention, especially in the skincare industry. Therefore, it is recommended that companies optimize their marketing strategies by leveraging celebrities with positive images and reliable consumer testimonials, particularly through social media and digital platforms, which are currently the primary communication channels for the target market.